2013
DOI: 10.1371/journal.pone.0082790
|View full text |Cite
|
Sign up to set email alerts
|

Association between the STK15 F31I Polymorphism and Cancer Susceptibility: A Meta-Analysis Involving 43,626 Subjects

Abstract: The association between the Serine/threonine kinase 15 (STK15) F31I polymorphism (rs2273535) and cancer susceptibility remains controversial. To further investigate this potential relationship, we conducted a comprehensive meta-analysis of 27 published studies involving a total of 19,267 multiple cancer cases and 24,359 controls. Our results indicate statistical evidence of an association between the STK15 F31I polymorphism and the increased risk of overall cancer in four genetic models: AA vs. TA+TT, AA vs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Our results showed that subjects with Phe/Ile genotype or at least one Phe allele had a significant reduced risk to breast cancer in Malaysian Chinese women even after Bonferroni correction, suggesting that it can be act as a strong protective biomarker for breast cancer in the population. This finding was similar to recent meta-analysis studies claiming that the Ile allele was an increase risk factor for breast cancer (Qin et al, 2013;Tang et al, 2013;Dai et al, 2014;Guo et al, 2014;Xu et al, 2014;Qin et al, 2015). In Malaysia, Malaysian Chinese women has the highest breast cancer incidences when compared to other ethnic groups (Leong et al, 2007;Pathy et al, 2011), and it is yet to clarify that the role of genetic abnormality contribute to the high incidence rate in this ethnic.…”
Section: 647 Association Of Cyp2e1 Stk15 and Xrcc1 Polymorphisms Wisupporting
confidence: 86%
“…Our results showed that subjects with Phe/Ile genotype or at least one Phe allele had a significant reduced risk to breast cancer in Malaysian Chinese women even after Bonferroni correction, suggesting that it can be act as a strong protective biomarker for breast cancer in the population. This finding was similar to recent meta-analysis studies claiming that the Ile allele was an increase risk factor for breast cancer (Qin et al, 2013;Tang et al, 2013;Dai et al, 2014;Guo et al, 2014;Xu et al, 2014;Qin et al, 2015). In Malaysia, Malaysian Chinese women has the highest breast cancer incidences when compared to other ethnic groups (Leong et al, 2007;Pathy et al, 2011), and it is yet to clarify that the role of genetic abnormality contribute to the high incidence rate in this ethnic.…”
Section: 647 Association Of Cyp2e1 Stk15 and Xrcc1 Polymorphisms Wisupporting
confidence: 86%
“…All statistical analyses described previously were performed in SAS 9.4 software (SAS Institute Inc., Cary, NC, U.S.A.). Using PS software (http://biostat.mc.vanderbilt.edu/twiki/bin/view/ Main/PowerSampleSize), the power value (α = 0.05) was calculated [27,28]. We also used the false-positive report probability (FPRP) to determine the significant findings [29].…”
Section: Methodsmentioning
confidence: 99%
“…Of the 96 articles that were initially identified in the search strategy, 80 studies were removed, including 3 duplicates, 77 studies during the title/abstract review, and 5 studies during the full-text review (Ewart-Toland et al, 2005;Couch et al, 2007;Qin et al, 2013;Tang et al, 2013;Xu et al, 2013) (Figure 1). Eleven studies satisfied all of the criteria and were included in this report (Dai et al, 2004;Egan et al, 2004;Sun et al, 2004;Lo et al, 2005;Cox et al, 2006;Fletcher et al, 2006;Tchatchou et al, 2007;Vidarsdottir et al, 2007;2010;Ruan et al, 2011;Shi et al, 2011).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%